Effects of modafinil and amphetamine on sleep-wake cycle after sleep deprivation in cats. - Hou Yi-ping; Lin Jian-sheng (Acta Pharmacologica Sinica, 2016)
AIM: The effects of modafinil and amphetamine on sleep-wake cycle and cortical power spectrum were assessed in the cats before and after sleep deprivation. METHODS: The sleep deprivation in the cats was used with the water tank technique. Cats were administrated with modafinil (5 mg.kg-1 p.o.) or amphetamine (1 mg.kg-1) before and after sleep deprivation. RESULTS: The waking effect of 8-10 h induced by modafinil before and after sleep deprivation was similar and was not followed by an increase in sleep rebound. On the contrary, the arousal effect about 8 h evoked by amphetamine after sleep deprivation was less lasting than that of 10-12 h observed in normal conditions and followed by an amplified rebound in both deep slow wave sleep and paradoxical sleep. CONCLUSION: These results suggest the efficiency of modafinil against somnolence and hypersomnia without increasing subsequent sleep.